Menara Sunway / Ahmad Izzulhafiz Musalakmal ... [et al.] - Ahmad Izzulhafiz, Musalakmal; Nasri Hazwan, Harizan; Nur Izzati Fadhlina, Roslan; Farah Lorita, Muhammad Ismail Noh; Nur Fatin Iwani, Roslan (2019)
This report is regarding on Menara Sunway that is located at Bandar Sunway, Petaling Jaya, Selangor. It involves all the maintenance system that is adapted in this building and information about the building. In this report, all information or data that has been collected is either through interview of the person in charge of the building or any other related resources. Interviewing is done by visiting Menara Sunway on the certain dates.